The spell of the sensuous : perception and language in a more-than-human world - Abram, David, 1957- (New York : Vintage books, 2017)
[In this book, the author] draws on sources as diverse as the philosophy of Merleau-Ponty, Balinese shamanism, Apache storytelling, and his own experience as an accomplished sleight-of-hand magician to reveal the subtle dependence of human cognition on the natural environment. He explores the character of perception and excavates the sensual foundations of language, which - even at its most abstract - echoes the calls and cries of the earth.
The ecology of magic, a personal introduction to the inquiry -- Philosophy on the way to ecology, a technical introduction to the inquiry -- The flesh of language -- Animism and the alphabet -- In the landscape of language -- Time, space, and the eclipse of the earth -- The forgetting and remembering of the air -- Coda, turning inside out.
boek
Keywords: Body, Human (Philosophy).; Human ecology; Perception (Philosophy).; Philosophy of nature